Visual ethics - Schwartz, Michael (College teacher); Harris, Howard (Head of Management Research); Comer, Debra R., 1960- (Research in ethical issues in organizations ;, 2018)
This volume includes six varied contributions to the study of visual ethics in organizations. The implications of our visual world for organizational life and personal behaviour have received scant research attention. This volume sets out to address that lack of research. It includes contributions on empirical studies, film, personal portraits, social research using the photo voice method, bureaucracy and critical theory. Contributors show how the application of disciplines developed for the study of films can help us to understand howorganizations are perceived, and how visual images can be used in empirical research about organizations, ethics and organizational citizenship behaviour. Some say philosophy has abandoned art, some that humans lack moral vision.A number of contributors show how a careful and informed study of art can enhance our understanding of organizational life. This volume seeks to put the visual back into ethics and organizations.